Comparative Analysis of Thermal Conditions and Comfort Between Modern and Traditional Districts in Hot-Arid Climate: Case Study in Ajman-UAE - Salameh, Muna (2023)
Passive design solutions play a pivotal role in fostering sustainable practices within traditional architecture, as they empower historical urban designs to harmoniously engage with their surroundings and weather conditions, particularly in hot regions such as the United Arab Emirates. This research followed a qualitative approach to propose modifications for the thermal conditions and comfort in the modern contemporary urban districts based on the positive strategies from old traditional ones in a Hot-Arid Climate - Ajman-United Arab Emirates (UAE) as a case study using ENVI-met software-microscale three-dimensional software model for simulating complex urban environments. Moreover, this study made an evaluation and comparison of the outdoor air temperature and thermal comfort between the traditional and modern urban districts to highlight the passive design solutions that increase the thermal effectiveness in the traditional urban fabrics, as some of these passive design solutions can be used to modify the thermal conditions in the modern ones. Additionally, the research output revealed that the traditional urban design has valuable, sustainable strategies, as there was a decrease in the maximum reading for the air temperature for the traditional Ajman heritage district compared to the modern district on the 21st of August - as a reference day- and that improved the thermal comfort in the outdoor open spaces too. In conclusion, the study results confirmed that the thermal conditions in the existing modern districts could be improved using passive design solutions such as shading devices and greenery. Finally, this research is expected to be a phase amongst different phases that can benefit urban designers and architects to adopt strategies from traditional and vernacular urban projects and merge them with contemporary modern urban design.